ปัจจัยที่มีผลต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐในจังหวัดปทุมธานี: Factors Affecting the Decision in Choosing Housing Loan Provided by Government Bank in Pathumthani Province - ดาวกลาง, วิมลรัตน์ (Journal of Applied Economics and Management Strategy, 2018)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาลักษณะด้านที่อยู่อาศัยของผู้ขอสินเชื่อในจังหวัดปทุมธานี และศึกษาปัจจัยที่มีผลต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐในจังหวัดปทุมธานี โดยกลุ่มตัวอย่าง คือ คนที่ทำงานในจังหวัดปทุมธานี จำนวน 440 คน สถิติที่ใช้คือ สถิติเชิงพรรณนา และ การถดถอยโลจิสติกส์ ผลการศึกษาพบว่า ลักษณะด้านที่อยู่อาศัยของผู้ขอสินเชื่อในจังหวัดปทุมธานีส่วนใหญ่เป็น ทาวน์เฮาส์ ทาวน์โฮม ร้อยละ 58.25 รองลงมาคือ ห้องชุด คอนโดร้อยละ 20 อาคารพาณิชย์ ร้อยละ 10.5 บ้านแฝด ร้อยละ 8.25 และ บ้านเดี่ยว ร้อยละ 3 ตามลำดับ ปัจจัยที่มีผลต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐในจังหวัดปทุมธานีแบ่งออกเป็น 3 ด้าน ได้แก่ 1) ด้านปัจจัยส่วนบุคคล ประกอบไปด้วย รายได้ 15,001-30,000 บ/ด. รายได้ 30,001-45,0000 บ/ด. มีผลในเชิงลบต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐ ส่วนช่วงอายุ 20-29 ปี การศึกษาต่ำกว่าปริญญาตรี มีผลในเชิงบวกต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐ 2) ปัจจัยด้านลักษณะที่อยู่อาศัยของผู้ขอสินเชื่อ ประกอบไปด้วย ประเภทที่อยู่อาศัย: ทาวน์เฮาส์ ทาวน์โฮม มีผลในเชิงบวกต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐ และ 3) ด้านการประเมินการให้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐ ประกอบไปด้วย วงเงินสินเชื่อสูงสุด อัตราดอกเบี้ย ระยะเวลาผ่อนชำระ ค่าธรรมเนียม พนักงานให้บริการดี มีผลในเชิงบวกต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐ ความรวดเร็ว การไม่บังคับทำประกัน การสนับสนุนวงเงินสินเชื่ออื่นๆ ความสะดวกในการติดต่อ คุณสมบัติผู้กู้ตรงตามกำหนด ทัศนคติที่ดีต่อธนาคาร และสื่อประชาสัมพันธ์ มีผลในเชิงลบต่อการเลือกใช้บริการสินเชื่อที่อยู่อาศัยกับธนาคารของรัฐ ณ ระดับนัยสำคัญทางสถิติที่ระดับ 0.05 This research is aimed at studying housing loan applicants in Pathumthani, namely, to examine factors affecting the decision in choosing housing loan provided by government banks in Pathumthani province and to provide information to the government banks as a guideline for improvement of their services to the people. The sample group is 440 workers in Pathumthani. The statistics used in this research are descriptive statistics and logistic regression. The study finds that 58.25% of housing loan applicants in Pathumthani are townhouses and townhomes, followed by apartments and condos accounting for 20%, commercial buildings for 10.5%, twin houses for 8.25% and single houses for 3%, respectively. There are 3 factors affecting the decision in choosing housing loan provided by government banks in Pathumthani province as follows: 1) Personal factors including income between THB15,001 – 30,000 per month and income between THB30,001 – 45,000 per month, all have negative impact on worker's decision to choose home loan from government bank. On the other hand, the age range of 20 – 29 years, education of below bachelor’s degree have positive impact. 2) Residential factors including residential types, which are townhouses and townhomes, have positive effect and 3) Bank customer satisfaction scoring shows that customers who are sensitive to high credit line, low interest rate, lenient repayment terms, low fees and good service of staffs, have positive preference for government bank services, while customers who value promptness, optional insurance, other credit support, ease of contact, borrowers’ qualifications, positive attitude towards banks, media and public relation, have negative preference for government banks at the 0.05 level of significance.